Usefulness of Pulsed-Field Gel Electrophoresis in Tracking Two Outbreaks of Invasive Meningococcal Disease Serogroup C in British Columbia. Issue 6 (2007) - Quan, Grahame; Gilbert, Mark; David, Samara T; Rahim, Tazim; Adie, Kathy; Shaw, Carol; McNabb, Alan; Isaac-Renton, Judy; Patrick, David M
Abstract : Two major outbreaks of invasive meningococcal disease serogroup C (IMD-C) were identified in British Columbia between 2000 and 2004. Pulsed-field gel electrophoresis (PFGE) and porA gene sequencing of all retained IMD-C isolates were used to assess correlations between genotypes and epidemiological patterns. PFGE patterns of IMD-C genotypes correlated with epidemiological patterns between 2000 and 2004 in British Columbia, and demonstrated that PFGE can identify outbreak-related cases. Both IMD-C outbreaks correlated with a respective PFGE pattern. PFGE analysis demonstrated that the 2004 British Columbia outbreak strain in men who have sex with men was closely related to the 2001 Abbotsford outbreak strain. PorA sequencing data indicated low diversity of class 1 outer membrane proteins in British Columbia, and did not correlate with epidemiological trends. There was a trend for outbreak-associated PFGE types to demonstrate higher case fatality rates.